ASSESSMENT OF SATISFACTION IN PATIENTS UNDERGOING SURGICAL TREATMENT BY THE WALANT TECHNIQUE - Marina Rafaele Makishi; Rafaela Amoedo Cox; Victor Spirandelli Pimentel; Yussef Ali Abdouni; Marcel Eiji Nakagawa (Acta Ortopédica Brasileira)
ABSTRACT Objective: To analyze the satisfaction of patients who underwent hand surgical treatment with the wide-awake local anesthesia no tourniquet (WALANT) anesthesia technique. Methods: This is a cross-sectional study on the satisfaction of patients who underwent hand surgical treatment with the WALANT technique. These patients were treated at the Hand and Microsurgery outpatient clinic of a public hospital from March 2020 to March 2022. They were assessed by the modified Heidelberg questionnaire. Results: The overall average of satisfaction totaled 3.27 (maximum value 4, SD 0.52, p-value 0.04), representing a good result. Patients’ profile characteristics showed no statistically significant differences. Conclusion: The efficiency of WALANT technique stemmed from the high satisfaction rate of patients undergoing minor surgeries, justifying its use as a routine option in outpatient surgeries in the public system. Level of evidence III, Retrospective comparative study.